2022
DOI: 10.3390/ijms24010147
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Immunogenic Tumor Antigens in Surrendered Immunity and the Significance of Autologous Tumor Cell-Based Vaccination in Precision Medicine

Abstract: The mechanisms by which immune systems identify and destroy tumors, known as immunosurveillance, have been discussed for decades. However, several factors that lead to tumor persistence and escape from the attack of immune cells in a normal immune system have been found. In the process known as immunoediting, tumors decrease their immunogenicity and evade immunosurveillance. Furthermore, tumors exploit factors such as regulatory T cells, myeloid-derived suppressive cells, and inhibitory cytokines that avoid cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 167 publications
0
7
0
Order By: Relevance
“…CD8 + cytotoxic T lymphocytes can recognize the antigenic targets presented on tumors and subsequently secrete cytokines to eliminate tumor cells. Meanwhile, helper CD4 + T cells play an equally important role in the immune response by preventing CD8 + cytotoxic T lymphocytes exhaustion and maintaining the cytolytic responses of CTLs [ 45 ]. These results suggested that Au/CuNDs-R848-mediated PTT/CDT can effectively stimulate in vivo anti-tumor T cell immunity.…”
Section: Resultsmentioning
confidence: 99%
“…CD8 + cytotoxic T lymphocytes can recognize the antigenic targets presented on tumors and subsequently secrete cytokines to eliminate tumor cells. Meanwhile, helper CD4 + T cells play an equally important role in the immune response by preventing CD8 + cytotoxic T lymphocytes exhaustion and maintaining the cytolytic responses of CTLs [ 45 ]. These results suggested that Au/CuNDs-R848-mediated PTT/CDT can effectively stimulate in vivo anti-tumor T cell immunity.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the present study observed higher immune scores and higher abundance of M1 macrophages, CD4 + T cells, CD8 + T cells and NK cells in the high-MLDIS group, further suggesting the influence of these tumor-infiltrating immune cells on melanoma development. High levels of infiltration of CD8 + T cells, CD4 + T cells, neutrophils, B cells, M1-polarized macrophages and dendritic cells determine the pre-existing anti-tumor immune activity of patients and are associated with better prognosis and longer survival in patients receiving immunotherapy [ 39 41 ]. MLDIS correlated significantly with the efficacy of anti-PD-1 therapy, and their high expression levels predicted good prognostic benefit.…”
Section: Discussionmentioning
confidence: 99%
“… 130 Immunotherapy’s potential is frequently undermined by an immunosuppressive milieu fostered by tumor-associated immune cells and the evasion of immune surveillance by tumor cells. 128 , 129 Consequently, the scientific community remains engaged in the development of more efficacious treatment strategies to augment therapeutic outcomes in oncology 131 , 132 ( Figure 6 ).…”
Section: Multimodal Killing and Therapeutic Effects Of Mofs On Tumor ...mentioning
confidence: 99%
“…Copyright 2022 American Chemical Society. 131
Figure 7 Schematic of ( A ) the fabrication process and ( B ) Cu-TCPC (Al) -Pt-FA stimulates the development of tumor immunity by depleting glutathione in cancer cells to enhance the effects of ROS and catalyzing O2 production by Pt NPs to reduce the inhibitory effect of tumor-induced hypoxic microenvironment on immune cells. Reprinted with permission from Chen Z, Wu Y, Yao Z, et al 2D Copper(II) metalated metal-organic framework nanocomplexes for dual-enhanced photodynamic therapy and amplified antitumor immunity.
…”
Section: Introductionmentioning
confidence: 99%